The relationship between maternal knowledge and timeliness of basic immunization in infants aged 0-12 months - Sulastri, Ai; Fadza, Ridzal (Program Studi Keperawatan, Politeknik Negeri Subang, 2024)
Background: The global infant mortality rate remains a significant concern, with a rate of 28.2 per 1,000 live births recorded in 2019. In Indonesia, the infant mortality rate reached 24 per 1,000 live births in 2022, and efforts to reduce this include immunization, as the World Health Organization (WHO) reports that around 1.5 million children die annually from preventable diseases, including a rising 15% mortality rate due to diphtheria in Indonesia in 2020. Purpose: To analyze the relationship between maternal knowledge and timeliness of basic immunization in infants aged 0-12 months. Methods: This study employs a quantitative research method with a correlational descriptive design and a cross-sectional approach, using purposive sampling to select a sample of 86 respondents. Data was collected through maternal knowledge questionnaires and observation sheets from mother and child notebooks, and the analysis was conducted using the Spearman test. Results: The study found that the majority of mothers, 40 respondents (46.5%), had good knowledge about basic immunization, followed by 30 respondents (34.9%) with adequate knowledge, and 16 respondents (18.6%) with insufficient knowledge. At Puskesmas Rawalele, almost all basic immunizations for infants aged 0-12 months were administered on time (76.7%), and there was a significant relationship between maternal knowledge and the timeliness of basic immunization, with a p-value of < 0.001. Conclusion: Maternal knowledge about basic immunization plays a crucial role in ensuring the timely administration of vaccines to infants. Consequently, public health initiatives focusing on increasing awareness and education about immunization among mothers could be instrumental in achieving higher compliance and better health outcomes for infants.